2015
DOI: 10.5204/intjfyhe.v6i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Engaging, supporting and retaining academic at-risk students in a Bachelor of Nursing: Setting risk markers, interventions and outcomes

Abstract: Student attrition from nursing programs impacts on sustainability of the profession. Factors associated with attrition include: lack of academic capital, extracurricular responsibilities, first generation tertiary students, and low socioeconomic or traditionally underrepresented cultural background. Successful Australian government reforms designed to advance equity in higher education have increased student population diversity, which is accompanied by a rise in the incidence of risk factors for attrition (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(58 reference statements)
0
14
0
1
Order By: Relevance
“…It remains unknown whether rural students’ cumulative experiences influence stress responses differently. Potential factors could include dislocation from home, financial pressures and reduced academic capital in their social networks leading to academic stress 31. Although some studies suggest that students in their first year of university studies experience higher levels of stress, it is well recognised that the transition to clinical training is stressful for medical students 32.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown whether rural students’ cumulative experiences influence stress responses differently. Potential factors could include dislocation from home, financial pressures and reduced academic capital in their social networks leading to academic stress 31. Although some studies suggest that students in their first year of university studies experience higher levels of stress, it is well recognised that the transition to clinical training is stressful for medical students 32.…”
Section: Discussionmentioning
confidence: 99%
“…As this study demonstrated, and literature supports, students frequently do not seek out help from educators until it is too late to alter a declining academic situation (Jeffreys, 2014). What constitutes an at-risk student may be related to grades, attendance, participation, or the educator recognizing a pattern of behaviour (Tower et al, 2015). This early and proactive intervention may best be delivered as a form of feedback that supports careful self-appraisal and builds self-efficacy and study habits (Bulfone et al, 2019;Lammers, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…A proactive stance is also needed for educators to actively support at-risk students early in a nursing program (Elliot, 2016;Harding, 2012;Jeffreys, 2014;Liem & Martin, 2012;Tower et al, 2015). Proactive strategies to identify students early and provide interventions at key transitional times in a program can work to prevent failure or withdrawal (Jeffreys, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further implication evidenced by the improvement in the 2017 CFY cohort's WAM is that holistic, integrated support is more beneficial than a subject-based approach, although any intervention appears to be better than none, including contact via SMS and email. The integrated model described here provides an important point of difference to similar programs used at other universities (Barnes et al, 2015;Nelson et al, 2009;Potter & Parkinson, 2010;Tower, Walker, Wilson, Watson, & Tronoff, 2015), which typically identify and support students on the basis of individual subjects. Even those examining the student experience across multiple subjects typically report their data on an individual subject basis, which we believe may conceal the benefits that come from taking a whole-ofstudent approach to appreciative advising modelled here in the CFY example.…”
Section: Concluding Discussionmentioning
confidence: 99%